Knee injuries in football – types, circumstances, impact and prevention - Salamon, Dariusz; Stachowiak, Julia; Sosin, Julia; Pilarz, Anna; Zwierzchowska, Maria; Sojka, Aleksandra; Domagała, Wojciech; Sobik, Klaudia (Quality in Sport, 2024)
Football is a globally popular sport with millions of participants, including professional and amateur players, who face a high risk of injuries, particularly to the knee joint. This study explores the impact of football on knee injuries, detailing knee anatomy, common injuries, their circumstances, treatment methods, and preventive measures. Key findings reveal that knee injuries are prevalent in football, with a significant portion being severe, leading to substantial downtime for players. Effective prevention strategies, such as pre-season preparations and injury prevention programs like FIFA 11+, are critical in reducing injury rates and ensuring players’ long-term performance and career longevity. AIM OF THE STUDY: The aim of the study is to summarize the available knowledge on the most common knee injuries in soccer and highlight their circumstances, impact on the health and careers of soccer players, and injury prevention options. SUMMARY: Football’s global appeal sees over 270 million participants, with a significant number engaged at professional levels, heightening their risk of injuries due to the sport’s physically demanding nature. The knee joint, a modified hinge joint comprising bones, ligaments, menisci, and other structures, plays a crucial role in football-related movements, making it susceptible to injuries. Data from various studies highlight the prevalence and severity of knee injuries in football. UEFA reports knee injuries accounting for 12-17% of all injuries, with severe cases leading to over four weeks of absence. The injury rate is notably higher during matches than training, emphasizing the need for robust preventive measures.